Characterization of high density polyethylene (HDPE) reinforced with banana peel fibers - Pereira, Paulo Henrique Fernandes [UNESP]; Carvalho Benini, Kelly Cristina C. [UNESP]; Watashi, Cintia Yumi [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Cioffi, Maria Odila Hilario [UNESP] (My University, 2013)
Lignocellulosic fibers from banana peels were washed with water in order to increase their compatibility with a polymeric matrix, and their properties were compared with unwashed fibers. Washed banana fibers were mixed with high density polyethylene (HDPE) and placed in an injector chamber to produce specimens for tensile tests. Samples of washed bananafibers/HDPE composites were characterized by tensile tests and thermal analysis. The chemical composition of unwashed and washed banana fibers was analyzed by thermogravimetric analysis, scanning electron microscopy, and X-ray diffraction. The treatment with water was effective at removing extractives and increasing the surface roughness, thereby increasing the thermal stability of the fibers. However, results showed that the addition of washed banana fibers decreased the thermal stability of composites, while increasing the melting and crystallization temperatures of composites. The addition of 5 wt% fibers also provided an improvement in mechanical properties of composites in comparison with pure HDPE.
Keywords: Banana peel fibers; Composites; High density polyethylene; Thermal analyses; Banana peels; Chemical compositions; High density polyethylene(HDPE); Lignocellulosic fibers; Melting and crystallization temperatures; Polymeric matrices; Properties of composites; Unwashed fibers; Composite materials; Fibers; Fruits; High density polyethylenes; Mechanical properties; Scanning electron microscopy; Surface roughness; Tensile testing; Thermoanalysis; Thermodynamic stability; Thermogravimetric analysis; Water treatment; X ray diffraction; Reinforced plastics; Gravimetry; Mechanical Properties; Polyethylene; Scanning Electron Microscopy; Tensile Tests; Thermal Analysis; Water Treatment; X Ray Diffraction